Health literacy screening in pediatric oncology and stem cell transplant caregivers: A cross-sectional cohort study. Issue 28 (1st October 2022) - Foti, Alycia R; Beauchemin, Melissa Parsons; Yao, Yujing; Jin, Zhezhen; Kahn, Justine
Abstract : 155 Background: Despite advances in childhood cancer outcomes, disparities among socially vulnerable populations persist. Associations between educational attainment, English proficiency and outcomes suggest that factors impacting communication and comprehension may contribute. Health literacy (HL) is the degree to which individuals can process and act on health information. It is reported that up to 35% of adults in the U.S. have limited HL, with prevalence rising to 50% in those from low-income households. While studies from medical oncology report associations between limited HL and inferior outcomes, there remains a paucity of data on HL rates and associated outcomes in pediatric oncology and stem cell transplant (SCT) populations. We evaluated HL rates in a group of pediatric oncology and SCT parents/caregivers at a large academic medical center, and explored associations with self-reported demographics. Methods: English or Spanish-speaking parents of children (1 – 18 years) receiving chemotherapy or SCT were eligible. Self-reported sociodemographics were collected via survey, and HL was measured via bilingual interview using the Newest Vital Sign screening tool. Scores indicating likelihood of limited (0 – 1), moderate (2 – 3) and high (4 – 6) literacy were calculated and associations between HL, demographics, social determinants of health, and clinical characteristics were explored. Results: In total, 48 caregivers had evaluable HL and demographic data; 33% were Hispanic, 27% were non-Hispanic Black, and 25% were Spanish speaking only; 53% had public insurance, and 12% did not complete high school. Forty-four patients (90%) had cancer, 51% of whom had leukemia or lymphoma. Mean HL score was 3.27 (+/- 1.90). Nine caregivers (18%) had limited HL, 18 (37%) had moderate HL, and 21 (43%) had high HL. When comparing the limited/moderate HL group to the high HL group in univariate analysis, a significantly higher proportion of those in the limited/moderate group were Spanish speaking only (p = 0.035), received less than a high school education (p = 0.002), were unemployed (p = 0.038), and endorsed material hardship (e.g., food insecurity) (p = 0.001). Across all participants, 69% sought information about their child's diagnosis from providers, and 55% sought information from the internet. Conclusions: Among this diverse population of pediatric oncology and SCT caregivers, over 50% are at risk of limited HL. Univariate models indicate that limited literacy is associated with Spanish language preference, low educational attainment, and material hardship, however larger patient numbers are needed to evaluate adjusted associations. Analyses measuring the contribution of HL to clinical outcomes are ongoing, with early results indicating that interventions addressing both material hardship and limited literacy are urgently needed.